Chapter New Lenses An Introduction to Innovations in Peace and Education Praxis - McInerney, William W. (Taylor & Francis, 2023)
In this chapter, the editors provide an overview of Innovations in Peace and Education Praxis. First, the chapter situates the book within the peace and education literatures. Drawing attention to calls for transdisciplinary scholarship and new lenses for peace education praxis, this chapter highlights how the book seeks to navigate through existing absences in the field, interrogate limits, open space for new and generative work, and reflect on their implications for scholars, researchers, students, practitioners, and educators. Second, the chapter reviews how the edited collection was developed, the influence of the Cambridge Peace and Education Research Group (CPERG), and why the process of creation was as important as the final product. Third, the chapter outlines the book's theoretical contributions to peace and education including its examination of transdisciplinary scholarship, praxis beyond binaries and rooted in ontological justice, second-order reflexivity, and an expansion of epistemological horizons beyond cognitive-centred modes of knowledge and representation. Finally, the chapter introduces each of the subsequent ten chapters that follow. The editors argue the new lenses brought forward do not offer templated answers but rather a constellation of insights, questions, challenges, and innovative examples of praxis which might help us collectively imagine new paths forward.